A dinâmica intraurbana de Goianira no contexto da Região Metropolitana de Goiânia - ANJOS, Antonio Fernandes dos (2009)
The socioespacial trajectory of the city of Goianira, state of Goiás/Brazil demonstrates the absorption power that the Brazilian metropolises exert on the neighboring cities. The present study of case aims to clarify how was the sprouting of the city of Goianira, in the 1920s, when it was only a village, and how it became an Goiânia's residential extension from the mid- 1970s on. In order to this, the first chapter provides the initial arrangement of the council, highlighting the constraints of their local and regional development, contextualizing it in the metropolitan dynamic. The second chapter presents a proposal of periodization of urban sprawl, divided into three spatial-temporal patterns of appearance and occupancy of lots of land. The third chapter presents the current situation of rural areas and the result of the strong influence of the metropolis on the socio-intraurban structure of the city, especially on the collective use of equipment, on the jobs and services given to society. It follows that the economic agriculture activity was gradually replaced by urban work, which is almost completely linked to the metropolis, considering that the residents of the city daily move in search of work, properties, leisure and services in the metropolitan center . The urban network has expanded, until connecting with the others cities, as a side effect of restricting the opening of new lots in the capital, Goiânia. Thus, Goianira, today, is a city that, both in social as space point of view, it's shown itself as a result of the answers it has gave to the Goiânia's needs. Thus, the Metropolitan Area of Goiânia is shown as an united 'body city', where some functions are developed by peripherals municipalities, especially the housing function